Empirical study on the influence of country-of-origin on consumers' perception towards their purchase intention of Malaysia's Halal food products - Said M.; Hassan F.; Musa R. (2023)
The country-of-origin (COO) of a product would have an effect on consumers' product evaluation and their subsequent purchase behavior directly and indirectly through beliefs [1, 2 and 3]. Inferences (previous experience and usage of brand) and country of origin (COO) can affect how people evaluate products [4]. The rapid increase of the global demand for Halal food means that there are millions of Moslem consumers with money to spend are looking for food that complies with the Islamic requirements. The main question arises is whether they would consider Malaysia-Halal food products in their Halal food purchase decision. A study was conducted among the participants of an international Halal forum in London and Malaysia to uncover their perception towards Malaysia and its Halal food products. The results of 264 respondents show that different nationalities have different perception towards Malaysia in general, its products and specific Malaysia s Halal food products. 2011 IEEE.